An improved two-parameter omega technique (itpot) for molecular orbital calculatlons (1983)
Bond lengths are calculated for tweive aromatic hydrocarbons by way of the ITPOT and a modified Coulson's equatlon. Comparlsons are made with respect to other theoretlcal results as well as with avallable experimental data. The predlctive capabiilties of the ITPOT and the modified Coulson's equatlon are pointed out.